CD147 Protein Expression and Temozolomide Resistance in Glioma Cells: An Ex vivo and In vivo Study: CD147 Expression and Temozolomide Resistance - Luo, Guo-Qiang; Bai, Shuang; Hu, Yan; Chen, Hu; Yan, Zhong-jun; Fan, Ling-ling (Cellular and Molecular Biology, 2022)
It has been noted that temozolomide resistance occurs in a number of malignancies, including glioma, although the underlying cause of this is unknown. The goal of the study in vivo investigation to show that increased CD147 expression in glioma cells is a factor in their resistance to the chemotherapy drug temozolomide. Proliferation assays, TUNEL assays, reactive oxygen species assays, protein degradation assays, immunohistochemistry, Western blotting, quantitative polymerase chain reactions, and tumorigenicity assays were all carried out. Using the human protein atlas databases, the expression levels of CD147 in different kinds of malignancies were examined. For immunohistochemistry, a total of 7, 12, 19, 15, and 16 glioma samples were taken from para-carcinoma tissue, representing stage I, stage II, stage III, and stage IV gliomas, respectively. The expression of CD147 proteins is correlated with the tumor's aggressiveness. Cell development was slowed by suppressing the expression of the CD147 protein. The expression of the CD147 protein contributed to the emergence of temozolomide resistance. Expression of the CD147 protein reduced mRNA expression. The growth-inhibitory impact of temozolomide on glioma cells was enhanced by the suppression of CD147 protein. Nuclear factor E2-related factor 2 expression and CD147 protein expression showed a significant reciprocal connection with each other (p 0.0001, r2 = 0.3254). In glioma, resistance to temozolomide is due to overexpression of CD147 protein and induction of nuclear factor E2-related factor 2.